Thiol/Disulfide Balance in Patients with Familial Hypercholesterolemia. (12th June 2018) - Şimşek, Özgür; Çarlıoğlu, Ayşe; Alışık, Murat; Edem, Efe; Biçer, Cemile Koca
Abstract : Objective . Herein, we investigated the balance of thiol/disulfide, with the hypothesis that the balance between disulfides and thiols, which are natural antioxidants, might be disrupted in patients with familial hypercholesterolemia, which eventually leads to endothelial damage. Methods . In this study, we evaluated 51 patients diagnosed with familial hypercholesterolemia and 81 healthy subjects. Blood samples were taken from the patients after a minimum of 12 hours of fasting; samples were immediately centrifuged, stored in Eppendorf tubes, and preserved at −80°C. Results . This study found that thiol levels are significantly lower in patients with familial hypercholesterolemia, whereas disulfide levels are higher (independent of age, gender, and body mass index). This means that in such patients, the thiol/disulfide balance changes in favour of disulfide. Conclusions . In this study, we found that the thiol/disulfide balance in patients with familial hypercholesterolemia is disrupted in favour of disulfide.